EFL Students’ Anxiety in Oral Presentation in Thesis Examination during Covid- 19 Pandemic Era at Islamic Higher Education - Rosmini Rosmini; Geminastiti Sakkir; Andi Anto Patak (Journal of Excellence in English Language Education, 2022)
This research aims to investigate the anxiety of EFL students in oral presentation in thesis examinations. The researchers employed qualitative research with a case study approach. Seven experienced EFL students have participated and the researchers employed a thematic analysis technique to analyze the data. The findings revealed that all EFL students are anxious in oral presentation in thesis examination, those are facilitative anxiety and debilitative anxiety. Students are categorized as facilitative anxiety when students are self-confident and studying beforehand while students are categorized as debilitative anxiety when they feel tense, worried, scared, nervous, self-doubt, blank, and tremble.